Associations of Electric Shock and Extremely Low-Frequency Magnetic Field Exposure With the Risk of Amyotrophic Lateral Sclerosis: The Euro-MOTOR Project. Issue 4 (10th January 2019) - Peters, Susan; Visser, Anne E; D'Ovidio, Fabrizio; Beghi, Ettore; Chiò, Adriano; Logroscino, Giancarlo; Hardiman, Orla; Kromhout, Hans; Huss, Anke; Veldink, Jan; Vermeulen, Roel; van den Berg, Leonard H; et al.
Abstract: We explored the associations of occupational exposure to extremely low-frequency magnetic fields (ELF-MF) and electric shocks with the risk of amyotrophic lateral sclerosis (ALS) in a pooled case-control study (European Multidisciplinary ALS Network Identification to Cure Motor Neurone Degeneration (Euro-MOTOR)) of data from 3 European countries. ALS patients and population-based controls were recruited in Ireland, Italy, and the Netherlands between 2010 and 2015. Lifetime occupational and lifestyle histories were obtained using structured questionnaires. We applied previously developed job exposure matrices assigning exposure levels to ELF-MF and potential for electric shocks. Odds ratios and 95% confidence intervals were estimated by means of logistic regression for exposure to either ELF-MF or electric shocks, adjusted for age, sex, study center, education, smoking, and alcohol consumption and for the respective other exposure. Complete occupational histories and information on confounding variables were available for 1, 323 clinically confirmed ALS cases and 2, 704 controls. Both ever having had exposure to ELF-MF above the background level (odds ratio = 1.16, 95% confidence interval: 1.01, 1.33) and ever having had potential exposure above background for electric shocks (odds ratio = 1.23, 95% confidence interval: 1.05, 1.43) were associated with ALS. Adjustment for the respective other exposure resulted in similar risk estimates. Heterogeneity in risks across study centers was significant for both exposures. Our findings support possible independent associations of occupational exposure to ELF-MF and electric shocks with the risk of ALS.